2008
DOI: 10.1007/s00203-008-0402-6
|View full text |Cite
|
Sign up to set email alerts
|

Ignicoccus hospitalis and Nanoarchaeum equitans: ultrastructure, cell–cell interaction, and 3D reconstruction from serial sections of freeze-substituted cells and by electron cryotomography

Abstract: Ultrastructure and intercellular interaction of Ignicoccus hospitalis and Nanoarchaeum equitans were investigated using two diVerent electron microscopy approaches, by three-dimensional reconstructions from serial sections, and by electron cryotomography. Serial sections were assembled into 3D reconstructions, for visualizing the unusual complexity of I. hospitalis, its huge periplasmic space, the vesiculating cytoplasmic membrane, and the outer membrane. The cytoplasm contains Wbres which are reminiscent to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 46 publications
4
70
0
2
Order By: Relevance
“…This interaction could involve injection of nutrients from Thermoplasmatales cells into ARMAN, parasitism of ARMAN, or exchange of molecules between them. Notable features distinguishing ARMAN-Thermoplasmatales interactions from those reported previously for N. equitans and I. hospitalis (10,11,14) include the rarity of cell-to-cell interactions and the cytoplasmic connection between ARMAN and the associated cell.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This interaction could involve injection of nutrients from Thermoplasmatales cells into ARMAN, parasitism of ARMAN, or exchange of molecules between them. Notable features distinguishing ARMAN-Thermoplasmatales interactions from those reported previously for N. equitans and I. hospitalis (10,11,14) include the rarity of cell-to-cell interactions and the cytoplasmic connection between ARMAN and the associated cell.…”
Section: Resultsmentioning
confidence: 74%
“…The ultrasmall archaeal parasite Nanoarchaeum equitans has only 552 genes and requires a connection to its archaeal host, Ignicoccus hopstialis, to survive (10). Recently, it was shown that this interaction involves contact between outer membranes (14). Given the vast diversity of microbial life (15), it is likely that other unusual relationships critical to survival of organisms and communities remain to be discovered.…”
mentioning
confidence: 99%
“…These two membranes enclose an intermembrane compartment with a variable width from 20 to 500 nm, resulting in a volume exceeding that of the cytoplasm (5). Its low electron density suggests that it is devoid of cellular material like ribosomes or DNA, and it was therefore named "periplasm" (7). The inner membrane, called the cytoplasmic membrane, releases numerous vesicles into the periplasmic space and also engulfs vesicles into the cytoplasm (7).…”
Section: T He Hyperthermophilic Crenarchaeon Ignicoccus Hospitalis Kimentioning
confidence: 99%
“…Cells were prepared for transmission electron microscopy as described in detail elsewhere (7,28). In brief, for visualizing whole cells, cells in suspension were chemically fixed by adding glutaraldehyde (final concentration, 2%), concentrated by brief centrifugation, applied to carbon-coated copper grids, and shadowed with 1 nm Pt/C (angle, 15°).…”
Section: Rhodopirellulamentioning
confidence: 99%